The Norton/Grove concise encyclopedia of music - Sadie, Stanley; Latham, Alison (W.W. Norton, 1988)
Entries for 4,500 composers, 2,000 terms, 1,100 performers, 1,000 titles of musical works, and 150 work-lists for major composers.